The Authority of Seneca in the Early Christian Argumentation - Nehring, Przemysław (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The paper deals with the authority of Seneca as employed by the eminent early Christian writers in their apologetic as well as polemical works.